Peeking behind the curtain: Unboxing science teacher educators’ subjectivities in continuous professional development programmes - Bravo González, Paulina De los Angeles; Galdames Poblete, Sergio Ignacio (Perspectiva Educacional, 2023)
Several research agrees on the contribution of continuous professional development (CPD) programmes to support curriculum reform. In Latin-America there is growing concern about the university-school relationship, mostly related to the CPD of teachers. In Chile, the relationship university-school is posed in institutional discourses as a desirable professional development goal, yet the importance is less recognised in practice. Considering the teacher educators’ subjectivity in higher education is barely explored in the teacher education literature leaves the question of who are those involved in CPD programmes? Taking a qualitative approach and using dialogical strategy, we study the design meetings of a university team/teacher educators leading a CPD programme in science. Findings show salient features of the teacher educators’ subjectivity produced around the interaction between the school and the higher education sector, their relationship among themselves, the conditions of the university, and their perception of schoolteachers. Implications to research and practice are discussed.